The Evolution of Regime Change and Information Warfare in the 21st Century - G. Simons (Международная аналитика)
Although information is nothing new to war or conflict, the speed at which it reaches a much wider target audience, and thus its potential impact and consequences, is changing due to the rapid development of information and communications technology. Regime change and information warfare have been around for a very long time in the history of organised human societies. An undertaken review of academic literature demonstrates a great interest today to these concepts in academic, policymaking and practical terms. The present article attempts to track the evolution of the Western conceptual and theoretical thinking on the use of regime change and information warfare, seeking to understand the factors that precipitate it. In the paper I address the following, what is the relationship between information warfare and regime change? The high level of information and communications technology development and persisting leadership globally have allowed the United States to engage in regime change and information warfare more effective, although not without risks. The author considers the most illustrative examples of such engagement and, based on them, concludes that we have seen a shift in motivation from an offensive stance (the desire to spread influence) to a defensive one (the desire to prevent other international actors from gaining influence and power) on the global level. The theoretical method chosen for the analysis is phenomenology, as a means of the reading and analysis of a lived experience as well as a qualitative method will be used to analyse the data, where the goal is to capture the complexity of the object of study.